Factors influencing the attainment to non-attainment of C1 level among students of the bachelor’s degree in English at a private university: A narrative study - Solano Vargas, Juliana Andrea; Bustos Buelvas, Ruth Sarai; Quintero Ararat, Evelin Yulieth (Corporación Universitaria Minuto de Dios – UNIMINUTO, 2025)
This qualitative study aims to investigate, through the lens of student experiences, the factors of attainment or not attainment faced by ninth-semester students at a private university in Bogotá to achieve the C1 level of English proficiency, a requirement for graduating with a bachelor's degree (ELT). Through semi-structured interviews, conducted with a population of 10 participants, key factors influencing the development of C1 level proficiency were identified: autonomy, effective learning strategies, quality of teaching, the language studied, emotional factors, social relationships, and self-perception. Furthermore, the importance of the teaching role and its direct impact on the acquisition process was highlighted, as well as the creation of immersive environments in the English language, since it was identified as a fundamental pillar for obtaining the C1 level. The findings inform evidence-based solutions gathered from students' experiences to improve language teaching, learning, and ultimately, C1 level attainment. Finally, the implications of this study are far-reaching, influencing English language education theory and practice. They not only enrich our understanding but also pave the way for future research such as curriculum design, teacher training, among others, ensuring academic and professional success in a globalized environment among students

Este estudio cualitativo tiene como objetivo investigar, a través de las experiencias estudiantiles, los factores de logro o no logro que enfrentan los estudiantes de noveno semestre de una universidad privada de Bogotá para alcanzar el nivel C1 de dominio del inglés, requisito para graduarse como licenciados. A través de entrevistas semiestructuradas, realizadas a una población de 10 participantes, se identificaron los factores clave que influyen en el desarrollo del dominio del nivel C1: autonomía, estrategias efectivas de aprendizaje, calidad de la enseñanza, la lengua estudiada, factores emocionales, relaciones sociales y autopercepción. Además, se destacó la importancia del rol docente y su impacto directo en el proceso de adquisición, así como la creación de ambientes inmersivos en el idioma inglés, ya que se identificó como un pilar fundamental para la obtención del nivel C1. Los hallazgos informan soluciones basadas en evidencia recopiladas de las experiencias de los estudiantes para mejorar la enseñanza, el aprendizaje y, en última instancia, el logro del nivel C1. Finalmente, las implicaciones de este estudio son de largo alcance, influyendo en la teoría y la práctica de la educación del idioma inglés. No sólo enriquecen nuestra comprensión, sino que también abren el camino para futuras investigaciones como el diseño curricular y la formación docente, entre otras, garantizando el éxito académico y profesional en un entorno globalizado entre los estudiantes
To identify and analyze the personal and institutional factors that contribute to the success or failure of ninth-semester students in achieving C1 language proficiency in an ELT degree at a private university in Bogotá, through semi-structured interviews, focusing on the students' experiences.
Keywords: English language education; CEFR C1 level achievement; English major university students; Language proficiency achievement; Narrative inquiry; enseñanza del idioma inglés; estudiantes universitarios; investigación narrativa; Ingles - Enseñanza; Esrudiantes Universitarios; Lenguas Germanicas